Independent role of CT chest in COVID-19 prognostication : Evidences from machine learning classification.: Role of CT chest in COVID-19 - Bhandari, Sudhir; Shaktawat, Ajit Singh; Tak, Amit; Patel, Bhoopendra; Gupta, Jitendra; Gupta, Kapil; Kakkar, Shivankan; Shah, Kshitij Darshan; Arora, Ayesha; Dube, Amitabh (Scripta Medica, 2021)
Background: The current coronavirus disease-19 (COVID-19) pandemic call attention to the key role informatics play in healthcare. The present study discovers an independent role of computerised tomography chest scans in prognosis of COVID-19 using classification learning algorithms.Methods: In this retrospective study, 57 RT PCR positive COVID-19 patients were enrolled from SMS Medical College, Jaipur (Rajasthan, India) after approval from the Institutional Ethics Committee. A set of 21 features including clinical findings and laboratory parameters and chest CT severity score were recorded. The CT score with mild, moderate and severe categories was chosen as response variable. The dimensionality reduction of feature space was performed and classifiers including, decision trees, K-nearest neighbours, support vector machine and ensemble learning were trained with principal components. The model with highest accuracy and area under the ROC curve (AUC) was selected.Results: The median age of patients was 55 years (range: 20-99 years) with 37 males. The feature space was reduced from 21 to 7 predictors, that included fever, cough, fibrin degradation products, haemoglobin, neutrophil-lymphocyte ratio, ferritin and procalcitonin. The linear support vector machine was chosen as the best classifier with 73.7 % and 0.69 accuracy and AUC for severe CT chest score, respectively. The variance contributed by first three principal components were 97.5 %, 2.4 % and 0.0 % respectively.Conclusion: In view of low degree of relationships between predictors and chest CT scan severity score category as interpreted from accuracy and AUC it can be concluded that chest CT scan has an independent role in the prognosis of COVID-19 patients.
Keywords: Classification; COVID-19; Chest CT scan; Machine learning; Pandemic